Gagasan Dasar Mengenai Etika dan Negara Menurut Plato (Sebuah pengenalan awal filsafat politik klasik) - Muhammad Fadil (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
To study politics and states in recent time mostly follows to what also happens empirically and has comprehensive topics such as democratization and civil society. However, to understand politic and growing 'state could not be separated from its philosophical views such as how people are just or unjust. Classical studies about state and politic offered by Plato, in spite of its great differences to modem theories, have its contribution to political studies, especially its moral and ethic to the statesman.